POLICY AND MARKET FOR WIND ENERGY IN THE UNITED KINGDOM - Buckley, JR (185P -3466)
UK energy policy includes a target to obtain 15% of electricity from renewables sources by 2015, increasing to some 20% by 2020. Support for energy RD&D continues, while wind energy has reached the position of commercial deployment supported by a Renewables Portfolio System (RPS) and the Renewables Obligation (RO). Proposed adjustments to the operation of the RO have increased the commercial attractiveness of offshore wind development.  With measures to address practical issues including grid connection and planning consenting, the deployment of onshore and offshore wind is accelerating:  2,200 MW of capacity is operational, 1,400 MW is under construction, and some further 7,000 MW is consented or in planning.  Round three of offshore wind licensing is expected to result in a further 13,000 MW of capacity.  Specialised capabilities to support these developments already represent a new branch of industry.